Prevalence of obstructive airway disease in pulmonary function tests of patients visiting respiratory medicine out patient department - S., Thritia; Deshmukh, Hafiz; Deshmukh, Ashish; Jadhav, Sunil; Kasat, Shivprasad; Roy, Arya; Mani, S. Thamil (International Journal of Research in Medical Sciences, 2023)
Background: The recognition of obstructive airway disease as a public health problem, however, has failed to keep pace with its increasing impact on health-care resources. This study is conducted to evaluate the prevalence of obstructive airway disease in pulmonary function tests (PFT) of patients visiting respiratory medicine out patient department (OPD). Methods: This is a retrospective study of patients from October 2020 to September 2022 (2 years), on 80 subjects reporting to respiratory medicine OPD, MGM medical college, Aurangabad. Data collected from 80 subjects who were diagnosed with obstructive airway disease in PFT. Results: The study population had a COPD prevalence of 16 (19.7%). GOLD criterion revealed that 54.2% (9/16) of COPD patients had mild COPD. This research showed no evidence of very severe COPD. In terms of gender distribution, 8 (16.6%) of 46 males and 7 (19.5%) of 34 women had COPD. However, there was no statistically significant (p=0.167) difference in COPD prevalence between sexes. Furthermore, univariable analysis revealed no significant differences in marital status (p=0.836), co-morbidities (p=0.541), family size (p=0.535), educational status (p=0.827), employment status (p=0.643), and medical visits (p=0.366) between persons with and without COPD. Conclusions: According to the findings of this research, the variables that increase a person’s likelihood of developing COPD are as follows: advancing age, prolonged exposure to smoke from biomass burning, tobacco use, and inadequate ventilation in the kitchen.